Penerapan Model Project Based Learning Berbantuan Quizizz dan Google My Maps Untuk Meningkatkan Kemandirian Dan Hasil Belajar Peserta Didik - Intivia Sholekah Asmara Putri; Singgih Prihadi (GEADIDAKTIKA, 2025)
This study aims to improve student independence and learning outcomes through the implementation of the Project Based Learning (PjBL) model assisted by Quizizz and Google My Maps on the material of Maps, Remote Sensing, and Geographic Information Systems in class X 1 of SMA Islam Diponegoro in the 2023/2024 academic year. This study uses a classroom action research design implemented in two cycles with 21 students as subjects. Data were collected through observations, tests, questionnaires, interviews, and documentation, with the validity of results, processes, catalysts, dialogic, and democracy. Data analysis was carried out quantitatively and qualitatively. The results showed that the implementation of PjBL assisted by Google My Maps was able to improve student learning independence. The completion of independent learning increased from 29% in the pre-cycle to 67% in cycle I, and reached 90% in cycle II. In addition, the implementation of PjBL assisted by Quizizz has been proven to improve learning outcomes, as seen from the increase in learning outcome completion by 67%, namely from 19% in the pretest to 67% in cycle I, and increasing to 86% in cycle II. Thus, the PjBL model based on the use of technology has been proven effective in improving student independence and learning outcomes.